New kid on the block: perineal stapled prolapse resection (PSP) is it worthwhile in the long-term? - Hummel, Bianka; Hardt, Julia (Langenbeck's archives of surgery, 2016)
Purpose: Perineal stapled prolapse resection (PSP) has been described as a new surgical treatment for external rectal prolapse in 2008. Short-term and midterm results acknowledged PSP as a safe, fast and simple procedure for high-risk patients. This study aims to assess long-term results after PSP. Methods: All patients who underwent PSP from 2007 to 2015 were analyzed retrospectively. Data was gathered from medical records and operative reports and by interviews with the general practitioner or the patient. Results: Indication for PSP was provided in 64 cases. One procedure had to be changed to an Altemeier’s and another to a laparoscopic rectopexy. The median age was 79.9 years (range 25.9-97.5). Spinal anaesthesia was used in 19 patients. The median operation time was 32.5 min (range 25-51.2). There was no mortality. One patient had to be reoperated. All other complications were minor. The median hospital stay was 6.0 days (range 2-23). Median follow-up of patients alive was 6.0 years (range 0.2-8.4). The 5-year recurrence-free survival rate for primary prolapse was 70.1 % compared to 34.3 % for recurrent prolapses (p = 0.048). Further positive prognostic factors were specimen length over 8 cm and lack of preoperative obstructed defecation syndrome. Faecal incontinence was remedied in 18, and new onset was recorded in 6 patients (significant incontinence rate reduction (p = 0.025)). Conclusion: Due to low morbidity and the possibility of spinal anaesthesia, PSP is suitable for frail patients. The recurrence rate for primary prolapse is similar to alternative perineal procedures like Delorme’s and Altemeier’s, but inferior to the laparoscopic techniques.
Gesehen am 18.06.2019